FERTILITY IN WOMEN WITH HEREDITARY BREAST AND OVARIAN CANCER - Vladimirovna, Boskhomdzhieva Mira; Arkadyevich, Nikolaev Alexander; Vyacheslavovna, Ploskonos Maria (International Journal of Research -GRANTHAALAYAH, 2025)
Among the causes of breast cancer and ovarian cancer in women, mutations of the BRCA1/2 genes have been characterized in detail. However, the effect of BRCA1/2 gene mutations on female fertility remains controversial. The purpose of this review is to assess the relationship between the BRCA1 and BRCA2 mutation status and female fertility in its various manifestations. A number of scientists consider mutations of the BRCA1/2 genes as a negative factor that reduces the reproductive abilities of women. A study of BRCA1/2 mutations in oocytes showed the possibility of spontaneous inactivation of the X chromosome, which can lead to infertility of female offspring, as well as a significantly reduced ovarian reserve and low oocyte yield. There are studies devoted to the assessment of gene expression in young and old oocytes, which showed a decrease in protein expression by DNA repair genes in parallel with age in rodents, cattle and humans. A series of studies confirm a significant decrease in the number of follicles in women carriers of BRCA1/2. There is an opinion that mutations of the BRCA1/2 genes do not affect the fertility of women carriers of these mutations. These studies are based on epidemiological and demographic data. A number of scientists attribute the presence of BRCA1\2 mutations to factors that increase fertility. They base their point of view on the longer telomeres in the reproductive cells of mutation carriers. In mutation carriers, the average telomere length is significantly longer than in their relatives who are not carriers (P = 0.0018), especially in families with BRCA2 mutations (P = 0.0016). The authors of the studies rely on such a well-known phenomenon as antagonistic pleiotropy. The mechanisms linking BRCA1 and BRCA2 mutations with female fertility remain a subject of debate and have not been fully studied. Animal model studies may reveal new mechanisms by which BRCA1/2 gene mutations affect female fertility.